PENGEMBANGAN E-MODUL INTERAKTIF MATERI TEKNIK DASAR KUDA-KUDA DAN POLA LANGKAH PENCAK SILAT KELAS VII SMP - Komang Sudiarta; I Gede Suwiwa; Ni Putu Dwi Sucita Dartini (Jurnal IKA, 2022)
This research development of science technology, information, and communication indirectly affect the learning media to support the learning process, one of them is the PJOK material. This research aimed to develop an interactive e-module for the basic techniques of stances and the pattern of pencak silat steps for class VII Junior High School students. This research used the development research with the ADDIE research model which consists of five stages, including, the analysis, design, development, implementation, and evaluation. Data was collected using a questionnaire and the data analysis technique used was quantitative descriptive analysis. Based on the results of product validation carried out by learning experts, the percentage value of content/learning materials experts consisted of 95% very well qualified, the learning design experts are very well qualified consisted of 92,5%, the learning media experts are very well qualified consisted of 97,5%, and expert practitioners consisted of 96,7% very well qualified in the field. Based on product trials, the percentage of individual trials consisted of 96,1% with very good qualifications, in small group trials with very good qualifications consisted of 93,5%, and in field trials with good qualifications consisted of 86,1%. It can be concluded that this interactive e-module is suitable to be used as a medium for learning of pencak silat in class VII Junior High School students.